INTRAKSI GURU PAI DAN SISWA DALAM MEMBENTUK KEPRIBADIAN MUTHMA’INNAH SISWA - Desy Nur Safitri; Ali Mu’tafi; Hidayatu Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to: (1) Examine the interaction between Islamic Religious Education (IRE) teachers and Grade VII B students at SMPN 1 Mojotengah; (2) Explore how the interaction between IRE teachers and students contributes to the development of *muthma’innah* (serene and composed) personalities among the students; and (3) Identify the supporting and inhibiting factors faced by IRE teachers in shaping students' *muthma’innah* personalities. This research employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The data analysis process involves data reduction, data presentation, and drawing conclusions or verification.The findings indicate that: (1) Interaction between IRE teachers and students occurs both inside and outside the classroom, through activities such as discussions, presentations, Q&A sessions, as well as group prayers (Dzuhur), mutual assistance, and the 6S values (Smile, Greet, Address, Shake hands, Courtesy, and Politeness); (2) In developing students’ *muthma’innah* personalities, teachers use key indicators such as inner peace and tranquility, awareness in embracing faith-based values, positive behavior and noble character, self-control and purity of heart, and strong social interaction skills; (3) Supporting factors include the availability of adequate facilities and open teacher-student communication, while inhibiting factors include environmental personality differences and lack of student attention and participation during learning activities.